REALIZING INCLUSIVE PUBLIC SERVICES: “LAPO BRA” INNOVATION IN BUILDING A LITERACY CULTURE FOR PERSONS WITH DISABILITIES IN MALANG CITY - Iswanto, Denny; Pamungkas , Dewi Bayu; Nurani , Farida (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
Today, public demand for effective, efficient and inclusive services to the government is getting higher and requires a change in the way the government works by innovating in providing inclusive services. The inclusiveness of public services is defined as the provision of services to the public in general, whether or not they have special needs, which are organized into a systemic unit in order to provide opportunities for the development of their potential. One of the innovations made by the Malang City Government in realizing inclusive services is the Braille Corner Service (Lapo Bra). This program was taken as a step to realize the spirit of equality for all citizens in obtaining rights in the fields of literacy and education. The purpose of this study was to identify and analyze the government's efforts in providing literacy services for persons with disabilities in the city of Malang. This study uses the Systematic Literature Review (SLR) research method of identifying, reviewing, evaluating, and interpreting all available research topics of interest to phenomena. The results of the study indicate that there have been fulfillment of inclusive service aspects from Lapo Bra services in Malang City. It still needs to be further developed towards adaptive services.